MICROBIOLOGICAL AND CHEMICAL ASPECTS OF DRINKING WATER AND TREATMENT ENHANCED ITS QUALITY - Zia, Muhammad Anjum; Khalil-ur-Rehman; Anjum, Fozia; Latif, Rizwana (Journal of Research (Science), 2005)
The present study was undertaken to determine the suitability of ground water of Faisalabad city for drinking purpose and the treatment was applied on the samples to remove the impurities. Total forty-five samples, 15 from each of the three colonies of Faisalabad (Gulistan colony No. 2, Taj colony and Maye-de-Jhugi) were collected. pH of the samples was found to range from 6.6-7.2 while electrical conductivity from 1.0-3.2 dS m-1. The dissolved oxygen for the water samples ranged from 3.7-5.7 mg L-1. The chemical oxygen demand gives the high COD values of the samples that are not safe. The total dissolved solids showed very high values that ranged from 1000-6666 mg L-1. Hardness and bacterial examination also showed very high values in samples. The treatment of activated carbon, hydrogen-zeolite and chlorination was applied to remove bacteria, colored compounds and hardness from the water samples, to provide better purity of water. Therefore, the results showed that there was a great contamination in ground water of the under studied colonies.